Prioritizing food security and livelihoods in climate change mitigation mechanisms: Experiences and opportunities for smallholder coffee agroforestry, forest communities and REDD+ - Davis, Alicia; Méndez, V.E. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Growing attention to climate change around the world has led to a wide array of policy measures to mitigate its effects. In the tropics, this has led to the proposal of mechanisms to change land use patterns in order to reduce carbon emissions, or promote carbon capture and storage. The rural communities that depend on these resources have increasingly been included in discussions around these mechanisms, in the hopes that rural development could be promoted simultaneously with climate change mitigation. Success in achieving these dual goals has been elusive however, driving continued debates around which territories, actors and mechanisms are best suited to support these efforts.